MONITORING OF STRONTIUM-90 GROUND SURFACE POLLUTION - HUDZENKO, V.; LOZYTSKA, N.; DOBROVOLSKYI, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The possibility of the terrestrial clam-shells and hens’ eggs application for the monitoring of daylight surface contamination by 90Sr had been considered. The coefficient of the transfer from the specific activity of shells to the areal contamination dencity had been calculated. For some patterns the ratio of 90Sr/226Ra activities in the objects under study had been determined. The possibility of the simple β-counters use for radiostrontium concentrations’ determination in the shells, collected in the areas influenced by Chernobyl disaster, had been demonstrated.